On the Nitrous Oxide Accumulation in Intermediate Waters of the Eastern South Pacific Ocean - Carrasco, Cristina; Karstensen, Johannes; Farias, Laura (Frontiers in Marine Science, 2017)
Nitrous oxide (N2O) is a powerful greenhouse gas principally produced by nitrification and denitrification in the marine environment. Observations were made in the eastern South Pacific (ESP), between 10º and 60°S, and ~75° to 88°W, from intermediate waters targeting Antarctic Intermediate Water (AAIW) at potential density of 27.0-27.1 kg m-3. Between 60° to 20°S, a gradual equatorward increase of N2O from 8 to 26 nmol L-1 was observed at density 27.0-27.1 kg m-3 where AAIW penetrates. Positive correlations were found between apparent N2O production (∆N2O) and O2 utilization (AOU), and between ∆N2O and NO3-, which suggested that local N2O production is predominantly produced by nitrification. Closer to the equator, between 20° and 10°S at AAIW core, a strong N2O increase up to 75 nmol L-1 was observed. Because negative correlations were found between ∆N2O vs. NO3- and ∆N2O vs. N* (a Nitrogen deficit index) and because ∆N2O and AOU do not follow a linear trend, we suspect that, in addition to nitrification, denitrification also takes place in N2O cycling. By making use of water mass mixing analyses, we show that an increase in N2O occurs in the region where high oxygen from AAIW merges with low oxygen from Equatorial Subsurface Water (ESSW), creating favorable conditions for local N2O production. We conclude that the non-linearity in the relationship between N2O and O2 is a result of mixing between two water masses with very different source characteristics, paired with the different time frames of nitrification and denitrification processes that impact water masses en route before they finally meet and mix in the ESP region.